Metode Pengukuran Kapasitansi Dengan Menggunakan Mikrokontroler Arduino Uno - Valentinus Galih Vidia Putra; Andrian Wijayono; Endah Purnomosari; Ngadiono Ngadiono; Irwan Irwan (Program Studi Pendidikan Fisika STKIP Nurul Huda, 2019)
RC circuit (Resistor-Capacitor) is an electric circuit that has a combination of resistor and capacitor components which are installed either series or parallel. This research was conducted to measure the capacitance of two capacitors with different capacitances with only using one resistor. This study aims to compare the capacitance both experimentally (using data acquisition systems) and theoretically. Capacitance measurements were carried out experimentally using Arduino Uno and at a maximum voltage of 5 volts. In this research, it has been successfully determined the charge capacitance of the capacitors, both in experiment and theory. It has been found the correlation of the results between experiment and theory (the value of R2 in charging and discharging process is greater than 0.95).